1992
DOI: 10.1093/wbro/7.1.95
|View full text |Cite
|
Sign up to set email alerts
|

PRIVATE INVESTMENT AND MACROECONOMIC ADJUSTMENT:A Survey

Abstract: This article reviews theories of investment behavior and examines empirical studies of investment in developing couintries. The emphasis is on understanding the interactions among macroeconomic policies, structural adjustment, and private investment. The article deals with the effect of exchange rate policy on investment, the relationship between public and private investment, the importance of market imperfections and financial constraints on capital formation, and the effect of economic instability on irreve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
2

Year Published

1994
1994
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(58 citation statements)
references
References 60 publications
2
54
0
2
Order By: Relevance
“…See, for example, Ramey and Ramey (1995), Aghion and Banerjee (2005) and Imbs (2006). 6 For example, Bernanke (1983), Pindyck (1991), Pindyck and Solimano (1993), Serven and Solimano (1992) and Blackburn and Varvarigos (2005) show that in models with investment irreversibility and financial frictions, higher uncertainty regarding investment prices will determine a lower level of investment and growth. Similarly, Furceri (2006) shows that in a model of embodied exogenous technological change, higher investment price uncertainty determines a reduction in the average rate of growth.…”
Section: Data and Empirical Methodologymentioning
confidence: 99%
“…See, for example, Ramey and Ramey (1995), Aghion and Banerjee (2005) and Imbs (2006). 6 For example, Bernanke (1983), Pindyck (1991), Pindyck and Solimano (1993), Serven and Solimano (1992) and Blackburn and Varvarigos (2005) show that in models with investment irreversibility and financial frictions, higher uncertainty regarding investment prices will determine a lower level of investment and growth. Similarly, Furceri (2006) shows that in a model of embodied exogenous technological change, higher investment price uncertainty determines a reduction in the average rate of growth.…”
Section: Data and Empirical Methodologymentioning
confidence: 99%
“…In this instance, investment decisions have two stages: first is the decision to expand the level of productive capacity, and second, is the decision about the capital intensity of the additional capacity (Serven and Solimano, 1992). The first decision depends on the expected degree of capacity utilisation in the economy, which provides an indicator of demand conditions, while the second decision depends on relative prices such as the cost of capital and labour.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The first decision depends on the expected degree of capacity utilisation in the economy, which provides an indicator of demand conditions, while the second decision depends on relative prices such as the cost of capital and labour. The investment decision takes place in a setting in which firms may be facing current and expected future sales constraints (Serven and Solimano, 1992). Therefore, investment depends both on profitability and on the prevailing sales constraints, which determine the rate of capacity utilisation (Serven and Solimano, 1992).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some empirical findings are inconsistent with the fact. (Green and Villanueva 1991, negative relationship between interest rate and investment, studies by others (Serven andSolimano 1993, Van wijubergen 1985) have shown that in repressed financial markets. Credit policy affects investment in a distorted manner.…”
Section: Interest Rate and Private Investment In Nigeriamentioning
confidence: 97%